2012
DOI: 10.1590/s0004-27302012000300009
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and laboratory features of children and adolescents with congenital hypothyroidism due to dyshormonogenesis in southern Brazil

Abstract: OBJECTIVE: To characterize the phenotype of patients with congenital hypothyroidism (CH) due to dyshormonogenesis, and to hypothesize on the degree of genetic defect. SUBJECTS AND METHODS: Patients with dyshormonogenesis were subdivided into G1 (radioactive iodine uptake, RAIU > 15%; n = 62) and G2 (RAIU < 15%; n = 32). Thyroglobulin (TG) was measured in all patients; perchlorate discharge test (PDT) was performed in G1; and saliva-to-plasma radioiodine ratio (I- S/P) in G2. RESULTS: Levels of TSH, TT4, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…In addition, average local wage as a confounding factor has a significant impact on the height and weight of children and adolescents; this study found that for every 10k CNY increase in local income, children and adolescents experienced an 0.6 cm increase in height and a 0.9 kg increase in weight. This is consistent with the findings of countries such as Japan that children from affluent families have better height and weight development than children from low-income families ( 26 , 38 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, average local wage as a confounding factor has a significant impact on the height and weight of children and adolescents; this study found that for every 10k CNY increase in local income, children and adolescents experienced an 0.6 cm increase in height and a 0.9 kg increase in weight. This is consistent with the findings of countries such as Japan that children from affluent families have better height and weight development than children from low-income families ( 26 , 38 ).…”
Section: Discussionsupporting
confidence: 91%
“…The U.S. Environmental Protection Agency (EPA) added perchlorate to its list of drinking water contaminants in 1998. Because perchlorate interferes with the synthesis, transport, function, and peripheral metabolism of thyroid hormones ( 26–28 ), thyroid hormones play an important role in metabolism and control of height and weight development, and long-term obvious thyroxine deficiency can seriously affect children’s height and weight development ( 29–31 ). Research has shown a decrease in thyroid hormone levels following exposure to perchlorate ( 3 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Over time, undiagnosed children appear lethargic, with slow movements, hoarse cry, feeding difficulties, constipation, macroglossia, umbilical hernia, large anterior or posterior fontanels, hypotonia, dry skin, thinning hair and typical facies with saddle nose. Some NBs with dyshormonogenesis present with a palpable goiter at birth, but this condition may also appear later, even with treatment (23). An x-ray of knee epiphyses may reveal delayed ossification, which reflects fetal hypothyroidism severity.…”
Section: Clinical Manifestations Of Chmentioning
confidence: 99%
“…And in these patients, the disorders may be either an anomaly of organification, storage or secretion (22,25). Organification disorders are the main disorders of hormonal synthesis, as noted by Cristina Romero et al in 2011 (22).…”
Section: Discussionmentioning
confidence: 97%